1965
DOI: 10.3758/bf03343211
|View full text |Cite
|
Sign up to set email alerts
|

Verbal mediation in reverse association: The role of temporal factors

Abstract: A three s tage reverse mediation paradigm, A-B, B-C, C-A and its control paradigm A-B, D-C, C-A, was studied at two test list anticipation intervals to determine the effects of temporal factors on reverse mediation. Forty-eight Ss learned three word lists consisting of low-frequency five letter words by the paired-associate method. The results indicated that temporal factors play a significant role in facilitating reverse mediation .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
1976
1976

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, the effect was enhanced when the mediator, B, was first a response and then a stimulus. Kulp and Robinson (1965) One group of the subjects learned the A-C list to a criterion of two perfect trials, while the other group was given 10 additional trials beyond the second perfect trial. Mediation was obtained in both groups, but the group that was given 10 additional trials reported significantly more awareness of the mediational process for the mediating pairs in the post-experimental inquiry.…”
Section: Later Studiesmentioning
confidence: 99%
“…However, the effect was enhanced when the mediator, B, was first a response and then a stimulus. Kulp and Robinson (1965) One group of the subjects learned the A-C list to a criterion of two perfect trials, while the other group was given 10 additional trials beyond the second perfect trial. Mediation was obtained in both groups, but the group that was given 10 additional trials reported significantly more awareness of the mediational process for the mediating pairs in the post-experimental inquiry.…”
Section: Later Studiesmentioning
confidence: 99%